2022
DOI: 10.3389/fpubh.2022.872974
|View full text |Cite
|
Sign up to set email alerts
|

How Do Intergenerational Economic Support, Emotional Support and Multimorbidity Affect the Catastrophic Health Expenditures of Middle-Aged and Elderly Families?–Evidence From CHARLS2018

Abstract: ObjectivesThe elderly face multiple vulnerabilities such as health, economy and society, and are prone to catastrophic health expenditures. This study aims to analyze the impact of children's intergenerational economic support, emotional support, and illness on the catastrophic health expenditures of middle-aged and elderly families.MethodsUsing China Health and Retirement Longitudinal Study (CHARLS 2018) data to calculate the catastrophic health expenditure of Chinese households as the dependent variable. Tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Older adults are vulnerable to health and economic issues, leading to potential health expenditures. It was found that the children’s intergenerational and emotional support will increase when catastrophic health expenditures occur in families with older adults ( 14 ). Furthermore, studies by Li et al ( 17 ) and Yang et al ( 27 ) also indicate that providing intergenerational support, encompassing both emotional and financial assistance, can have a positive impact on the health and well-being of older parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults are vulnerable to health and economic issues, leading to potential health expenditures. It was found that the children’s intergenerational and emotional support will increase when catastrophic health expenditures occur in families with older adults ( 14 ). Furthermore, studies by Li et al ( 17 ) and Yang et al ( 27 ) also indicate that providing intergenerational support, encompassing both emotional and financial assistance, can have a positive impact on the health and well-being of older parents.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding oral health, older adults require the assistance and support of their offspring concerning financial capacity, treatment accessibility, and emotional well-being. Monetary aid from their adult children bolsters the fiscal capability of older adults concerning the medical services they can afford ( 14 , 15 ). Caregiving by children enhances the ease of obtaining medical care for older adults, whereas emotional backing from offspring reflects the potential availability of medical resources for older adults ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Support from children includes financial, emotional, and instrumental support ( 50 , 54 , 55 ) respondents received in the last 12 months. Financial support was measured by the total amount of money and in-kind support respondents received from their children in the past year.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research con rmed that nancial aid from their offspring played a vital role in the quality of life for parents [22]. Tang et al proposed that emotional support from adult children were effective in reducing the risk of CHE in middle-aged and older families [23]. These studies have found that the daily care provided by adult children can improve the quality of life in older people.…”
Section: Introductionmentioning
confidence: 99%